Efficient enrichment of glycopeptides by supramolecular nanoassemblies that use proximity-assisted covalent binding. Issue 21 (25th September 2019) - Wang, Meizhe; Gao, Jingjing; Zhao, Bo; Thayumanavan, S.; Vachet, Richard W.
Abstract : Covalent capture and enrichment of glycopeptides for mass spectrometry analysis can be accomplished using supramolecular nanoassemblies that feature functional groups that accelerate the capture reaction. Abstract : Mass spectrometry (MS)-based analysis of glycoproteins and glycopeptides requires selective separation strategies to eliminate interferences from more abundant non-glycosylated biomolecules. In this work, we describe a two-phase liquid–liquid extraction method using supramolecular polymeric nanoassemblies that can selectively and efficiently enrich glycopeptides for enhanced MS detection. The polymeric nanoassemblies are made selective for glycopeptides via the incorporation of hydrazide functional groups that covalently bind to glycans. The enrichment efficiency is further enhanced via the incorporation of acidic functional groups that lead to a proximity-assisted catalysis of the hydrazide–glycan conjugation reaction. Our results further demonstrate the value of designer supramolecular nanomaterials for the selective enrichment of modified peptides from complicated mixtures.